Development of a master–slave robot system for farm operations - Noguchi, Noboru; Will, Jeff; Reid, John; Zhang, Qin (Computers and electronics in agriculture, 2004)
The primary objective of this study was to develop a control system for autonomous mobile robots used in farm operations. To accomplish this objective, it was necessary to develop mobile robots having minimal centralized control. This paper focuses on the development of two basic motion control algorithms, namely a GOTO algorithm and a FOLLOW algorithm, for use in a master–slave multi-robot system. These two robot motion control algorithms would have wide applicability in farm operations. The GOTO algorithm can be applied when the master wants the slave to go to a specific place, a certain distance from the current operational position. Safety is one important issue in controlling the master–slave system because the master and the slave move independently. In this GOTO algorithm, the slave was set to slow-down to allow the master pass the slave safely in case there was a potential collision due to path overlap in the field. The slave was also able to change its path to avoid a crash based on the collaborative GOTO algorithm. The FOLLOW algorithm allows for a more cooperative way to guide the slave to follow the master at a predetermined relative distance and angle, regardless of the traveling speed and direction. This FOLLOW algorithm incorporated a nonlinear sliding mode controller to provide a robust control for the slave. The validation tests indicated that the sliding mode controller could provide a better performance in terms of both lateral offset and spacing controls compared than using a conventional PD controller.